2009
DOI: 10.1080/09638280802354992
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of standard dysphagia treatment in first time documented stroke patients

Abstract: These results demonstrate that separate and specific dietary ratings in addition to the SFAM assistive/ independence levels are necessary to obtain a comprehensive assessment of the stroke patient with dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…55% of acute (60% of cases) and subacute (40% of cases) stroke could off the NG tube after participating in a conventional swallowing therapy. Total time of swallowing therapy in that study is 2–11 hours [ 27 ]. In a previous study that used an early swallowing therapy in acute stroke, 64% of patients who requiring NG tube were discharged with no NG tube [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…55% of acute (60% of cases) and subacute (40% of cases) stroke could off the NG tube after participating in a conventional swallowing therapy. Total time of swallowing therapy in that study is 2–11 hours [ 27 ]. In a previous study that used an early swallowing therapy in acute stroke, 64% of patients who requiring NG tube were discharged with no NG tube [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early screening for swallowing function after stroke is recommended; however, currently, there are no randomised controlled studies on the optimal timing of screening for swallowing function. 5 …”
Section: Rehabilitation Of Stroke Dysfunctionmentioning
confidence: 99%
“… 6 8 Effective rehabilitation is believed to shorten the course of this impairment, lighten the burden for both patients and society, and reduce the mortality rate. 9 11 A review by Cochrane from 2012 12 concluded that insufficient data remains related to swallowing therapy effects on functional outcome and death in dysphagic patients with either acute or subacute stroke, but behavioral interventions and acupuncture can reduce dysphagia. The standard swallowing training includes the most basic and traditional methods, involving compensation strategies such as postural adjustment or diet modification, strengthening weak oropharyngeal musculature through oral exercise, following oropharyngeal swallowing maneuvers to augment impaired anatomy, heightening sensory input through thermal-tactile stimulation, and developing a feeding-swallowing training program.…”
Section: Introductionmentioning
confidence: 99%